AFFECT OF FEEDING REGIME ON SURVIVAL AND GROWTH OF TOMATO ANEMONEFISH (AMPHIPRION FRENATUS BREVOORT 1856) JUVENILES - Loc, Ha Le Thi; Thuy, Nguyen Thi Thanh (Vietnam Journal of Marine Science and Technology, 2009)
Newborn Tomato Anemonefish (Amphiprion frenatus Brevoort 1856) from egg batch were divided into 4 treatments in triplicate. Open culture system included 15 liter glass tanks with 40 fish/tank. The fish were promptly separately fed with 4 different feeding regimes. The results showed that the survival of the fish fed on rotifers (Brachionus plicatilis) (5-7 ind./ml) combined with Nannochloropsis oculata (104-106 cells/ml) (after one day of hatching) and nauplii Artemia (57 ind./ml) (after three days of hatching) was significantly higher (70.83 to 72.50%) compared to those of the fish fed on nauplii Artemia instead of rotifers (10.83 to 27.50%). The average length of 30-day old fish fed on rotifers combined with Nannochloropsis oculata and nauplii Artemia (19mm) was significantly higher than those of the fish fed on comrnercial diet (Frippak 300) instead of nauplii Artemia (14mm). In addition, the 30 day old fish fed on rotifers was in similar length (SD: ±0.71 to ± 0. 74) compared to those of the fish fed on nauplii Artemia instead of rotifers (SD: ± 0.1 to ± 2.99).